Desain Panoramic Container Pool 2 In 1 Sebagai Sarana Peningkatan Kompetensi Underwater Welding di Jawa Timur - Amin Jakfar; Sahari; ANAUTA LUNGIDING Risdianto (G-Tech: Jurnal Teknologi Terapan, 2024)
East Java, especially Madura, has potential in the maritime sector, especially shipping. However, this condition is not supported by competent human resources. Especially in the field of underwater welding. In supporting efforts to improve the quality of human resources in the field of underwater welding. Panoramic Container Pool 2 In 1 is an alternative for improving the quality of human resources in the field of underwater welding. This study uses a qualitative method. Data collection was carried out by observation and literature review. In this research, we discuss the design of making an underwater welding pool that does not require expensive costs. The design of the Panoramic Container Pool 2 In 1 foundation is based on the soil structure on the Madura State Polytechnic campus, using a 40 foot container as the main material for construction, and is equipped with a control room which is useful as an effort to prevent incidents during underwater welding training.